Modeling the Structural-Thermal-Electrical Coupling in an Electrostatically Actuated MEMS Switch and Its Impact on the Switch Stability. (2nd September 2013) - Ouakad, Hassen M.; Younis, Mohammad I.
Abstract : Modeling and analysis for the static behavior and collapse instabilities of a MEMS cantilever switch subjected to both electrical and thermal loadings are presented. The thermal loading forces can be as a result of a huge amount of switching contact of the microswitch. The model considers the microbeam as a continuous medium and the electric force as a nonlinear function of displacement and accounts for its fringing-field effect. The electric force is assumed to be distributed over specific lengths underneath the microbeam. A boundary-value solver is used to study the collapse instability, which brings the microbeam from its unstuck configuration to touch the substrate and gets stuck in the so-called pinned configuration. We have found negligible influence of the temperature on the static stability of the switch. We then investigate the effect of the thermal heating due to the current flow on the cantilever switch while it is in the on position (adhered position). We also found slight effect on the static stability of the switch.